Let "9x-x^2=m" and "x+\\frac{1}{x}=n" , where "m" and "n" are integer numbers.
If "x" ≠"\\ 0" , then
"\\begin{cases}\n9x-x^2=m\n\\\\\nx+\\frac{1}{x}=n\n\\end{cases}\n\\quad \\Leftrightarrow \n\\quad\n \\begin{cases}\nx^2-9x+m=0\n\\\\\nx^2+1=nx \n\\end{cases}\n(1)\n\\quad \\Leftrightarrow \n\\quad \n\\begin{cases}-9x+m-1=-nx\n\\\\\nx^2-nx+1=0\n\\end{cases}"
"x(9-n)=m-1"
If "n=9" , then "m=1" and system of equations "(1)" is equivalent to "x^2-9x+1=0" .
"x_{1,2}=\\frac{9\\pm \\sqrt{81-4}}{2}=\\frac{9\\pm\\sqrt{77}}{2}" , and "(x_1)^2+(x_2)^2=\\frac{81+18\\sqrt{77}+77}{4}+ \\frac{81-18\\sqrt{77}+77}{4}=79"
If "n" ≠ "9" , then "x=\\frac{m-1}{9-n}" is a rational number.
"x" is one of the roots of "x^2-nx+1=0" . The roots are "x_{1,2}=\\frac{n\\pm\\sqrt{n^2-4}}{2}" .
We know, that "x" is rational, therefore "\\sqrt{n^2-4}" is integer, because square root of integer number is either integer or irrational. If it was irrational, then fraction "\\frac{n\\pm\\sqrt{n^2-4}}{2}" wouldn’t be a rational number.
So, "n^2-4=k^2" , where "k" is integer.
"n^2-k^2=4\\quad \\Leftrightarrow \\quad (n-k)(n+k)=4"
"n-k" and "n+k" are both even numbers (if they are odd, then their product is odd; if one number is odd and another one is even, then their sum is odd, but it is equal to "2n" )
We have two cases:
1) "\\begin{cases}\nn-k=2\n\\\\\nn+k=2\n\\end{cases}" and then "n=2", "k=0" .
2) "\\begin{cases}\nn-k=-2\n\\\\\nn+k=-2\n\\end{cases}" and then "n=-2", "k=0."
If "n=2" : "x^2-2x+1=(x-1)^2=0" and "x=1" . If this case "9x-x^2" and "x+\\frac{1}{x}" are integers.
If "n=-2" : "x^2+2x+1=(x+1)^2=0" and "x=-1" . If this case "9x-x^2" and "x+\\frac{1}{x}" are integers.
So, the sum of squares is "79+1+1=81"
Answer: the sum of squares of all numbers x such that both expressions "9x-x^2" and "x+\\frac{1}{x}" are integer numbers is equal to 81.
Comments
Leave a comment